(untitled) (Salam International Academic Journal, 2023)
Insurance is a contractual arrangement employed to safeguard one’s property from financial and economic risks while providing the insurer protection against unexpected losses. The primary objective of insurance is to mitigate financial losses and cover unforeseen expenses resulting from events such as accidents or fires. This system involves three key parties: the insured, the insurer, and the subject of insurance. The insurer, or insurance company, bears the responsibility for fulfilling the financial obligations of compensation. The insured, also known as the policyholder, can be either a natural person or a legal entity who commits to making specified payments in exchange for the acquisition of an insurance policy. In Afghanistan, insurance serves as a financial tool to shield against financial and economic risks, similar to its role in other countries. Various types of insurance are available in the country, including fire insurance, health insurance, and business insurance. Nevertheless, this study illustrates the legal aspects and the legal nature of insurance, as some religious scholars contend that insurance contracts are impermissible under Sharia law. The lack of awareness among the Afghan population about insurance has been a significant factor contributing to its limited growth. This study also delves into the legal framework surrounding insurance contracts and addresses associated concerns.